FORMATION OF SOCIAL EDUCATION FOR THE YOUNG GENERATION BASED ON THE REQUIREMENTS OF THE TIMES - Muratova Shakhnoza Ibatovna (Journals Park Publishing, 2024)
The article discusses the upbringing of the young generation. Opinions about a solid foundation for the formation of a young generation and a society with high intellectual potential are presented. Also, a new approach to the organization of important components of social education - intellectual, spiritual-ethical, physical, labor, aesthetic, legal, ecological, economic, sexual education, and ways of their effective organization in order for them to become well-rounded human beings. development is of particular importance.
Keywords: education, educational process, spiritual and moral, universal value, knowledge, skills, responsibility, science, social education, etiquette.